Conversion of Waste Corn Biomass to Activated Bio-Char for Applications in Wastewater Treatment - Karami, Shokooh; Papari, Sadegh; Berruti, Franco (Frontiers in Materials, 2022)
This study proposes the conversion of waste corn grains contaminated by deoxynivalenol (also known as vomitoxin), a mycotoxin produced by plant pathogens, into a value-added product. Batches of 500 g of contaminated corn grains were pyrolyzed in a batch reactor by thermal treatment at temperatures up to 500 ºC with a 15 °C/min heating rate and generating condensable vapors, gases and solid bio-char. The bio-char produced was subsequently activated in a furnace at 900 ºC, using CO2 as an activation agent, at different residence times. The effect of activation residence time on the characteristics of the activated bio-char, varying it from 0.5 to 3 hours, was investigated. Characterization tests included BET surface area, SEM, TG-FTIR, pH, and XRD on both bio-char and activated bio-char. BET results illustrated a significant increase of the surface area from 63 to 419 m2g-1 and pore volume from 0.04 to 0.23 cm3g-1 by increasing the activation time from 0.5 to 3 hours. SEM images visually confirmed a considerable increase in pore development. The pH significantly increased from 6 to 10 after activation, due to the elimination of acidic functional groups. The proximate analysis showed the stable carbon of the activated char reaching approximately 90 wt.%, making it promising for catalyst/adsorbent applications. The adsorption performance of activated bio-char was tested by utilizing three different model molecules with different characteristics: methylene blue, methyl orange, and ibuprofen. Among all activated bio-char samples, activated bio-char with 3 hours activation time showed the highest adsorption capacity, with a total adsorption (25 mg/g of activated bio-char) of methylene blue after 5 minutes. The results showed that the adsorption capacity of the activated bio-char was similar to that of valuable commercial activated carbon.